1991
DOI: 10.1111/j.1445-5994.1991.tb01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Oat bran and cholesterol reduction: evidence against specific effect

Abstract: Most placebo-controlled studies testing the hypo-cholesterolaemic action of oat bran have compared high fibre against low fibre diets. To determine whether oat bran had greater cholesterol-lowering action than another source of fibre (wheat bran) we compared the effect of breads of similar total fibre content containing either oat bran or additional wheat bran. Twelve hyperlipidaemic subjects (38-66 years) were stabilised on lipid-lowering diets for at least three months prior to the study. Subjects were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Diets enriched with a median dose of 3 Brown et al (79) were the first to undertake a comprehensive meta-analysis of all viscous, soluble fibre types on cholesterol. Although the main objective was to study the cholesterollowering effect of all viscous, soluble fibre types, it was, nevertheless, the first to consolidate data on oats and (24) 235 (235M:0F) P, 4 (40) 18 (13M:5F) 10 (12) 105 (56M:49F) 62 Subgroup and study, year (Reference) Hypercholesterolaemic Turnbull & Leeds, 1987-Glucan N Demark-Wahnefried et al, 1990Kestin et al, 1990Anderson et al, 1991Bremer et al, 1991Davidson et al, 1991Leadbetter et al, 1991Van Horn et al, 1991Lepre & Crane, 1992Stewart et al, 1992Uusitupa et al, 1992Whyte et al, 1992Noakes et al, 1996Johnston et al, 1998Romero et al, (b), 1998Onning et al, 1999Lovegrove et al, 2000Reynolds et al, 2000Van Horn et al, 2001Amundsen et al, 2003Berg et al, 2003Kerckhoffs et al, 2003Maki et al, 2003Biorklund et al, 2005Karmally et al, 2005Martensson et al, 2005Panahi, 2006…”
Section: Discussionmentioning
confidence: 99%
“…Diets enriched with a median dose of 3 Brown et al (79) were the first to undertake a comprehensive meta-analysis of all viscous, soluble fibre types on cholesterol. Although the main objective was to study the cholesterollowering effect of all viscous, soluble fibre types, it was, nevertheless, the first to consolidate data on oats and (24) 235 (235M:0F) P, 4 (40) 18 (13M:5F) 10 (12) 105 (56M:49F) 62 Subgroup and study, year (Reference) Hypercholesterolaemic Turnbull & Leeds, 1987-Glucan N Demark-Wahnefried et al, 1990Kestin et al, 1990Anderson et al, 1991Bremer et al, 1991Davidson et al, 1991Leadbetter et al, 1991Van Horn et al, 1991Lepre & Crane, 1992Stewart et al, 1992Uusitupa et al, 1992Whyte et al, 1992Noakes et al, 1996Johnston et al, 1998Romero et al, (b), 1998Onning et al, 1999Lovegrove et al, 2000Reynolds et al, 2000Van Horn et al, 2001Amundsen et al, 2003Berg et al, 2003Kerckhoffs et al, 2003Maki et al, 2003Biorklund et al, 2005Karmally et al, 2005Martensson et al, 2005Panahi, 2006…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies of the effect of β-glucan in oat and barley products on serum cholesterol levels have been reported over the ≈30 years since Anderson and colleagues (Anderson and Bridges 1993) first brought the potential cholesterol-lowering effect of oat bran to public attention. The magnitude of this effect has been variable and, in some cases, no statistically significant effect was reported (Swain et al 1990;Bremer et al 1991;Lovegrove et al 2000). This review emphasizes the role that the variability of the physicochemical state of the β-glucan in the foods may play, leading to either greater or lesser efficacy.…”
Section: Blood Lipidsmentioning
confidence: 99%
“…The consumption of bread providing 140 g of rolled oats per day led to an 11% reduction in serum total cholesterol concentrations [164]. However, other studies found no hypocholesterolemic effect of incorporating oats into bread [158, 165167]. Bread making can cause significant depolymerization of β -glucan, primarily induced by β -glucanase enzymes present in wheat flour [162, 168].…”
Section: Beta Glucan Obesity and Metabolic Syndromementioning
confidence: 99%